2020
DOI: 10.1089/ars.2020.8035
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Myeloid Cells and Noncoding RNA in Abdominal Aortic Aneurysm Disease

Abstract: Significance: Abdominal aortic aneurysm (AAA) is a potentially fatal condition, featuring the possibility of high-mortality rupture. To date, prophylactic surgery by means of open surgical repair or endovascular aortic repair at specific thresholds is considered standard therapy. Both surgical options hold different risk profiles of short-and long-term morbidity and mortality. Targeting early stages of AAA development to decelerate disease progression is desirable. Recent Advances: Understanding the pathomecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 163 publications
(231 reference statements)
0
10
0
Order By: Relevance
“…Some recent reviews summarized the impact of miRNA and long non coding RNA (lncRNA) in cellular processed involved in abdominal aortic aneurysm [ 34 , 35 , 36 , 37 , 38 , 39 ]. Although some lncRNAs have been described as dysregulated in models or human tissue of AAA, comparatively few studies exist to date that have established their functional roles in pathologic disease.…”
Section: Biomarkers and Compounds In Abdominal Aortic Aneurysms (Untreated Disease)mentioning
confidence: 99%
“…Some recent reviews summarized the impact of miRNA and long non coding RNA (lncRNA) in cellular processed involved in abdominal aortic aneurysm [ 34 , 35 , 36 , 37 , 38 , 39 ]. Although some lncRNAs have been described as dysregulated in models or human tissue of AAA, comparatively few studies exist to date that have established their functional roles in pathologic disease.…”
Section: Biomarkers and Compounds In Abdominal Aortic Aneurysms (Untreated Disease)mentioning
confidence: 99%
“…There are no clear and unified standards for the classification of LncRNAs. LncRNAs can be classified according to their relative positions to the coding genes and can thus be divided into five categories: sense lncRNAs: the transcription direction is the same as that of the neighboring mRNAs; antisense lncRNAs: the transcription direction is opposite to the transcription direction of the neighboring mRNAs; bidirectional lncRNAs, can be transcribed from the same and opposite directions as adjacent mRNAs at the same time; intergenic lncRNAs, produced by transcription between two genes; and intronic lncRNAs, produced by transcription from the intron region of genes ( 33 , 54 56 ). Furthermore, lncRNAs can be classified according to their respective role, which can be roughly divided into four categories: signal, decoy, guide, and scaffold molecules ( 32 , 57 64 ).…”
Section: Overview Of Lncrnasmentioning
confidence: 99%
“…In vivo and in vitro experiments additionally showed that Chi3l1 not only regulates cytokine synthesis and survival of macrophages but also promotes aortic smooth muscle cell migration and cytokine production, and stimulates adhesion molecule expression in vascular endothelial cells (145). A recent review focused on myeloic cells and aneurysm disease (146).…”
Section: Rna-based Therapy In Vascular Diseases Non-coding Rnas In Aaamentioning
confidence: 99%